Structural distortion and photoconductive modulation of La1-xYxCoO3 epitaxial films. Issue 3 (1st February 2022) - Wang, Lin; Liu, Haifeng; Yang, Jiacheng; Li, Jie; Sun, Yuxi; Jiang, Qin; Xie, Ruishi; Guo, Baogang; Zhang, Xingquan; Zheng, Kui
Abstract: In this work, we successfully prepared epitaxial La1-x Yx CoO3 (x = 0, 0.05, 0.1, 0.15) films on (100) SrTiO3 by polymer assisted deposition. The synergistic effect of biaxially tensile strain and doping yttrium on the structural distortion and photoconductive process of the films has been investigated. Due to lattice mismatch, the epitaxial strain along c -axis as well as the strain-induced tetragonal distortion of La1-x Yx CoO3 films increase with the content of doping yttrium. As-prepared films have higher degree of CoO6 octahedral distortion, i.e., Jahn-Teller-like tetragonal distortion, which result in lower crystal field splitting energy and narrower band gap energy, thereby elevating the charge transition. Additionally, increase of epitaxial strain leads to lower adsorption free energy in La1-x Yx CoO3 films, and results in the increase of chemisorbed oxygen, which is beneficial to electron transport in the process of light response. The introduction of new oxygen vacancy defect sites by doping Y 3+ ions and the proper amount of oxygen vacancy can effectively inhibit the recombination of the photo-induced electron-hole pairs, thus improving the activity for photoconductive response. The results reveal that the photoconductive properties of the as-prepared films are largely related to the synergistic effect of biaxially tensile-strained tetragonal distortion of CoO6 and doping yttrium.